(untitled) (Research, Society and Development, 2020)
The coronavirus pandemic (COVID-19) is the biggest public health emergency facing the world. Concerns vary regarding physical health, the psychological suffering that can be experienced by the general population and the elderly, considered this, the risk group with the highest number of deaths affected by the virus. The aim of the present study was to raise knowledge about the implications for the mental health of the elderly and the importance of fundamental rights in the current scenario of this pandemic. An exploratory literature review was carried out based on some reports from academics at the University of Maturity in Dianópolis-TO. Finally, some challenges for the practice of psychologists during and after the pandemic were discussed.